Analysis of Information Systems Development Methods: A Literature Review - Wiguna, Kevin; Mahdiana, Deni (Jurnal Inovtek Polbeng Seri Informatika, 2023)
The development of information systems encompasses a variety of approaches and platforms. These platforms or tools suitable for creating information systems include web-based, desktop-based, or mobile-based solutions. The Software Development Life Cycle (SDLC), specifically the process used to design and construct information systems, aims to deliver high-quality systems that align with customer preferences and the benefits of system creation. This research was carried out to establish a model for developing website-based information systems. The data for this model was gathered from pertinent literature spanning the years 2019 to 2023. The research methodology employed here is a Systematic Literature Review (SLR). SLR is a method used to identify, assess, and interpret all existing research within a specific subject area, focusing on topics of interest and research questions associated with a particular subject. The findings of this research highlight the primary approaches used in the development of website-based information systems, as well as the pros and cons of employing such systems, as demonstrated in this study. The research findings indicate that the most commonly used method in information system development is the waterfall method, with the education and business sectors being the most frequently focused areas.